Remote sensing supported analysis of soil salinity in Langkawi Island, Malaysia - Jusoff, Kamaruzaman; Yusoff, Mohd Kamil; Sulaiman, Wan Nor Azmin (1995)
Salt affected soils have received the attention of scientist and development workers throughout the world. In Malaysia, agriculture is of prime importance for the livelihood of the population. However, degradation of soils though salinity has been a major agricultural problem in some states. The high evaporation rate in combination with high water table causes salinity development in the northern part of Malaysia. Digital image processing techniques supported by visual interpretation and in-situ ground measurements as field checks were used to delineate and evaluate both qualitatively and quantitatively the salinity pattern at Langkawi Island, Kedah. This study attempted to classify the whole Langkawi Island according to various salinity levels based on surface soil resistivity survey using a grid approach of 13km2 interval. The resistivity was measured within the soil root zone of 0-15cm2. An empirical acquired ground measurement through multiple regression analysis was applied. The results showed that the correlation of Landsat TM data with actual salinity levels is high. The resulting regression model was used as a basis for generating digital cartographic product to depict salinity pattern over the entire island for optimum agricultural development zoning.